Displacement, Encroachment and Settlement: Interrogating Kyu in Peri‐Urban Yangon. (6th July 2020) - Roberts, Jayde Lin
Abstract: This article interrogates the meaning of kyukyaw, often shortened as kyu, a Burmese word that is used as both a verb—to occupy or encroach—and a noun—squatter or slum. This deployment of language demands attention because kyu evokes strong negative sentiments, despite its ambiguity. The rapid pace of change in post‐junta Myanmar has compelled both the elite and the marginalized to seek rightness through the notion of rule of law, even though customary practices have not adhered to the strictures of manmade law. Through the personal narratives of residents in Hlaingthaya Township in Yangon, this article raises questions about rightful settlement in unclear legal frameworks.